[PP.22.24] THE NEW CONTRASTING TRIAL AMONG BIOFEEDBACK OR TRADITIONAL CHINESE MEDICINE OF TIANMA GOUTENG DECOCTION AND L AMLODIPINE BESYLATE IN PATIENTS WITH ESSENTIAL HYPERTENSION. (September 2017) - Liu, Y.; Liu, W.; Fan, Y.; Du, L.F.; Peng, C.G.
Abstract : Objective: Objective: It is lack of contrasting trial among Biofeedback(B) or Triditional Chinese Medicine(TCM) of Tianma-Gouteng Decoction and L-amlodipine Besylate(L) in patients with essential hypertension without organ damages. Design and method: Group B of 62 cases were given biofeedback one time a day for 40 minutes, group TCM of 63 cases were took the water decoction tid for each time of 150 ml, group L of 65 cases were given the drug qd for 2.5 mg to treat for 4 weeks respectively. ABPM, CBP, symptoms and side effects were compared. Results: (1). The total effective rate of symptoms relieving for B, TCM and L were 82.2% (51/62), 95.2% (60/63) and 67.7% (44/65) (P < 0.05 or 0.01) respectively. (2). The average BP, BP load for 24 hr, daytime and nighttime after treatment were decreased (P < 0.05 or 0.01) in each group itself except average daytime DBP in group B, but BPV, HRV, nighttime BP drop rate, circadian rhythm of BP in each group were not interfered (all P > 0.05). (3). The descending amplitudes of SBP/DBP for 24 hr or daytime and DBP for nighttime after treatment in L were greater than other two groups (P < 0.05); The descending amplitudes of SBP/DBP for every period after treatment between group B and TCM were no difference (P > 0.05) except average daytime DBP in group B; The average nighttime SBP after treatment among three groups were no difference (P > 0.05). (4). CBP after treatment in each group itself were decreased (P < 0.05 or 0.01); The effective rate of 83.9% (52/62) in group B was greater than TCM of 66.7% (42/63) or L group of 69.2% (45/65) (P < 0.05). (5). There were adverse reaction rate of 4.8% (3/63) in TCM than 12.3% (8/65) (P < 0.05) in L. Conclusions: Biofeedback is similar to TCM but under L-amlodipine in ABP curative effect except poorer average daytime DBP and it is better than the other two groups in CBP curative effect, it is superior to L-amlodipine but inferior to TCM in relieving symptoms; TCM is optimal in relieving symptoms.